Doug Sutton interviewed by Maria Zann in the Mark Schuster and Maria Zann folklore collection. - Sutton, Doug, 1912-2008.; Zann, Maria; Schuster, Mark. (1993)
Folkloric recording.
Recorded on 20 July 1993 in Blackbutt, Queensland.
Digital master available
Summary not yet available.
Keywords: Sutton, Doug, -- 1912-2008 -- Interviews; Folk musicians -- Queensland -- Interviews; Folk dance music -- Queensland; Folk musicians